Size dependence of solute diffusivity and Stokes-Einstein relationship: effect of van der Waals interaction - Sharma, Manju; Yashonath, Subramanian (Diffusion Fundamentals, 2007)
Size dependence of solute diffusivity has been investigated using molecular dynamics simulations for a range of solute radii in a binary mixture consisting of solute and solvent species. We demonstrate that the Stokes-Einstein relationship between self diffusivity and solute radius breaks down over a range of solute-solvent size ratios. This is a result of the previously known Levitation Effect. Three distinct regimes can be seen depending on the solute-solvent size ratio. Several properties have been computed to understand the nature of solute motion in the three regimes.